The Important Role of Human Resource Management Practices, Worker Motivation, Leadership, Work Commitment, and Employee Performance - Muhammad Donal Mon; Jackson; Adi Neka Fatyandri (Jurnal Dinamika Manajemen, 2024)
The performance of a company can be seen from the performance of the human resources in it. Employee performance can be influenced by several supporting factors such as employee motivation, leadership, human resource management practice, and work commitment. This study aims to examine how human resource management practice, employee motivation and leadership impact employee performance with work commit-ment as an intervening variable. This research includes quantitative descriptive research using a questionnaire as a tool to collect data. The number of respondents in this study was 435 using purposive sampling method. Analysis using PLS with a predetermined research method to get the results of the study. Based on the test results obtained, HRMP has a positive effect on work commitment. Leadership, work commitment and work motivation have a positive effect on employee performance. HRMP has a positive effect on employee performance mediated by work commitment. Based on the results of existing research, it is necessary to conduct further research on other sectors other than the technology industry because this sector is quite different from other sectors.